2021
DOI: 10.17796/1053-4625-45.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Success of Biodentine and Ferric Sulfate as Pulpotomy Materials in Primary Molars: A Retrospective Study

Abstract: Objective: To determine the clinical and radiographic success of Biodentine® (BD) and Ferric Sulfate (FS) as primary molar pulpotomy materials and to compare their outcomes. Study design: Retrospective data was obtained from the electronic health records (EHR) of a university-based pediatric dental clinic. Participants were enrolled according to specified inclusion and exclusion criteria. Two trained and calibrated examiners evaluated the EHR using validated criteria for clinical and radiographic outcomes. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The application of biocompatible materials on the root pulp tissue can preserve vitality and stimulate the neoformation of mineralized tissue [2,3]. In the present study, we chose to compare MTA and BD since we can observe in the literature that they have similar clinical successes in approximately 100% of the cases [27,[30][31][32][33][34][35]. Recent studies demonstrate the clinical and radiographic success of teeth that underwent pulpotomy with MTA or BD [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The application of biocompatible materials on the root pulp tissue can preserve vitality and stimulate the neoformation of mineralized tissue [2,3]. In the present study, we chose to compare MTA and BD since we can observe in the literature that they have similar clinical successes in approximately 100% of the cases [27,[30][31][32][33][34][35]. Recent studies demonstrate the clinical and radiographic success of teeth that underwent pulpotomy with MTA or BD [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Reference [49] selected 71 primary molars with deep carious lesions, they performed pulpotomy with FS and they found that the overall success rate at 24 months follow up was 91.5%. Reference [50] divided 102 primary molars in two groups and they performed in the group of 79 teeth pulpotomy with FS and the results showed that the clinical and radiographic success rates of this group were 84% and 70% respectively. Also, worth mentioning is the pulpal response to the use of the FS as a pulpotomy agent from a histological sight.…”
Section: Ferric Sulfatementioning
confidence: 99%